Bank-Enforceable Title in the system of banking privileges: a study of the institution and its repeal - Pawełczyk, Mirosław (PRAWO i WIĘŹ, 2025)
The bank-enforceable title was one of the most significant banking privileges consisting of the power of banks to issue an enforcement title without trial. The bank-enforceable title was one of the most significant banking privileges consisting of the power of banks to issue an enforcement title without trial. The paper addresses the genesis, function and legal construction of the first and most controversial enforcement privilege in the Third Republic of Poland. The paper also discusses the formation of the discourse on the constitutionality of the bank-enforceable title.